Consideration of risk in PPP-projects - Zimmermann, Josef; Eber, Wolfgang (Business, Management and Economics Engineering, 2014)
Risk management has become a core competence for companies operating in construction services. In particular regarding Real Estate Development and Construction Management the fundamental knowledge and the dedicated ap- plication of risk assessment turn out to be critical. Construction Management deals with a multitude of local and temporal issues which are unknown or only given by statistical evaluation while conducting a unique construction project within a very tight frame of budget and time. Real Estate projects focus on the predictability of profitable operation for a fairly long period in advance and are therefore subject to many more and more voluminous uncertainties. With PPP-projects a more or less complete federal task is awarded to a private company. Its extent varies but com- prises at least design, construction and operation of a real estate project, e.g. a toll road, bridge, tunnel or other infrastructural object. Durations of such contracts of- ten extend to some 20 to 30 years. In this article the applicability of traditional means of risk management is inves- tigated for the use on PPP-projects and limits of risk consequences are pointed out. Finally we come to the conclusion, that the resulting unavertable risks tend to exceed every surcharge that could be successfully placed on a market.